On conceptual grounds of diagnostics and monitoring of geosystems - Shuman, V. (Geofizicheskiy Zhurnal, 2015)
Within the trend of ideas, methods and approaches of nonlinear dynamics basic features of geo-systems are being considered on high-quality level. It is noticed that evolution of processes and objects in lithosphere cannot be realized outside the limits of self-wave processes, which are spatial-temporal structures. It is remarkable that general trends of evolution of geo-systems can be interpreted in terms of geo-seismicity. We mean formation in geo-system of some generalized self-wave field, which is self-organized at the expense of energy and matter flows from the depth of the earth. Urgency of studies of synchronous dynamics of subsystems or elements of geo-medium, influence of noise on synchronization is being noticed. It is noteworthy that in this context tracking the spectrum of spontaneous seismic-acoustic and electromagnetic emission of lithosphere origin temporally and of spatial “bifurcations” of auto-structures which reflect evolution of seismic-tectonic systems producing seismic process become the first-rate task of modern experimental studies. It is probable that such an approach to formulation of aims, objects and ways of monitoring of evolution of geo-systems is not only necessary but inevitable because it allows to bring it nearer to experimental situation.